The Princeton companion to Atlantic history - Miller, Joseph Calder; Brown, Vincent, 1967-; Canizares-Esguerra, Jorge; Dubois, Laurent, 1971-; Kupperman, Karen Ordahl, 1939- (Princeton University Press, 2015)
This book, the first encyclopedic reference work on Atlantic history, takes an integrated, multicontinental approach that emphasizes the dynamics of change and the perspectives and motivations of the peoples who made it happen.